Tender is the flesh : a novel - Bazterrica, Agustina María, 1974- (Scribner, an imprint of SImon & Schuster, Inc., 2020)
"The electrifying, award-winning, internationally bestselling novel about a dystopian world in which animals have been wiped out, humans are being harvested for food, and society has been divided into those who eat and those who are eaten"--